Dismantling the World : The Capitalocene, Effective Constructivism, and the Inhuman (Das Questões, 2021)
An inhuman dimension haunts the world; but this dimension is repressed by what I call the effective constructivism, understood as what configures the world. Leaning on Moore’s analysis, first I will shed some light on the relation between the Capitalocene and effective constructivism. Using Haraway’s notion of the Chthulucene, in the second section I will break the plane of symmetry that effective constructivism produces between humans and nonhumans. In the third section, I will explain how the concept of the inhuman might be more efficient than the concept of the nonhuman to contest effective constructivism: the inhuman is the unconstructable part of the human that resists the humanist scheme at play in effective constructivism. In the last section, I will lean on Heidegger’s philosophy to imagine what dismantling the world of the Capitalocene could mean and why this dismantling might foster the decolonization of nature.